2020
DOI: 10.1111/1440-1681.13215
|View full text |Cite
|
Sign up to set email alerts
|

A directly GP130‐targeting small molecule ameliorates collagen‐induced arthritis (CIA) by inhibiting IL‐6/GP130 signalling and Th17 differentiation

Abstract: Rheumatoid arthritis is a chronic inflammatory disease associated with joint inflammation and destruction driven by T helper 17 (Th17) cells. Interleukin‐6 (IL‐6) is secreted by many cell types, including macrophages and synovial fibroblasts. It induces the differentiation and function of Th17 cells that can increase lymphocytic infiltration in the joint. LMT‐28 can suppress IL‐6 signalling through direct binding to glycoprotein‐130 and alleviate inflammatory diseases such as rheumatoid arthritis and inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Another small molecule inhibitor LMT-28 (a derivative of oxazolidinone) was recently demonstrated to suppress IL-6 signaling by directly binding gp130, resulting in alleviation of inflammatory diseases such as RA and inflammatory bowel disease (69). LMT-28 could also suppress the differentiation of pro-inflammatory Th17 cells in human PBMCs by blocking gp130 and its subsequent STAT3 signaling cascade, and it was proposed as a gp130-specific inhibitor for treatment of RA (70). The availability of gp130-specific inhibitors represents promising avenues for future investigations to therapeutically target gp130 in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another small molecule inhibitor LMT-28 (a derivative of oxazolidinone) was recently demonstrated to suppress IL-6 signaling by directly binding gp130, resulting in alleviation of inflammatory diseases such as RA and inflammatory bowel disease (69). LMT-28 could also suppress the differentiation of pro-inflammatory Th17 cells in human PBMCs by blocking gp130 and its subsequent STAT3 signaling cascade, and it was proposed as a gp130-specific inhibitor for treatment of RA (70). The availability of gp130-specific inhibitors represents promising avenues for future investigations to therapeutically target gp130 in SLE patients.…”
Section: Discussionmentioning
confidence: 99%
“…Single-use or combination treatment with LMT-28 (a derivative of oxazolidinone) and metformin significantly ameliorates arthritic signs in rats with CIA by suppressing Th17 differentiation and IL-6 signaling in FLS (66,67). A combination of LMT-28 and tetrahydropapaverine (THP, benzylisoquinoline alkaloid) could attenuate RA through the suppression of Th17 differentiation in T cells and proinflammatory cytokine-induced inflammation in FLS (68).…”
Section: Simultaneous Effect Of An Ra Drug On T Cells and Flsmentioning
confidence: 99%
“…According to previous studies, LMT-28, a derivative of oxazolidinone, has been shown to significantly inhibit IL-6 activity through direct binding to GP130 and is nontoxic with oral availability [11]. LMT-28 alleviated collageninduced arthritis and ameliorated the progression of pancreatitis in a mice model, and these two inflammatory diseases are related to an increase in IL-6 level [12]. This suggests that LMT-28 can be used to treat bone resorption in periimplantitis, which is also a type of inflammation with increased IL-6 level.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the effects of LMT-28 on bone resorption in peri-implantitis, an appropriate animal model is needed that can simulate human diseases, diabetes mellitus, dentition defects, and peri-implantitis. In this study, we chose Sprague-Dawley (SD) rats, which are an ideal model for implant placement and induction of peri-implantitis [12][13][14]. Because osteoblasts express a large amount of IL-6 and RANKL in LPS-induced bone resorption, we chose osteoblasts as the cells to study in vitro [15].…”
Section: Introductionmentioning
confidence: 99%